PERFORMANCE ANALYSIS OF EFFECT RATE OF CROSS LAYER BASED INTRUSION DETECTION FOR WIRELESS LAN - Kumar, Dr. Vinod; Singh, Mr Avtar; Narang, Mrs. Ritika (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Wireless ad-hoc networks are vulnerable to various kinds of security threats and attacks due to relative ease of access to wireless medium and lack of a centralized infrastructure. Security is an alarming concern, as everything being transmitted is available in the air. The current paper deals with Study of effect of rate on performance of cross layer based intrusion detection for WLAN reflects the significance of cross layer technique in detecting intruder on WLAN. Exploiting the information available across different layers of the protocol stack by triggering multiple levels of detection enhances the accuracy of detection. We validate our design through simulations and also demonstrate lower occurrence of false positives.